Iron modified biochar for soil improvement as well as preparation method and application of iron modified biochar

By reacting biochar with iron salt solution to prepare iron-modified biochar, the problem of insufficient adsorption capacity of biochar to phosphorus is solved, the sustained release of phosphorus in the soil and the prevention and control of water pollution is achieved, plant growth is promoted and phosphorus fertilizer is saved.

CN119318941APending Publication Date: 2025-01-17GUANGZHOU INST OF FORESTRY & LANDSCAPE ARCHITECTURE
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411409520.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing biochar has low adsorption capacity to phosphorus, and there are large differences between different types of biochar, making it difficult to effectively solidify phosphorus and prevent water pollution. Especially in urban landscape water bodies, excessive phosphorus can easily lead to water pollution.

Method used

Iron-modified biochar is prepared by soaking biochar in an acid solution and mixing it with the iron salt solution, reacting and calcining it thoroughly, and calcining it, improving its phosphorus adsorption capacity, and applying it to the soil to achieve sustained release and solid storage of phosphorus , prevent water pollution.

Benefits of technology

Iron-modified biochar significantly improves the adsorption and sustained release of phosphorus, effectively prevents water pollution, promotes plant growth, and saves the use of phosphorus fertilizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318941A_ABST
    Figure CN119318941A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of iron-modified biochar, which comprises the following steps: soaking biochar in an acid solution, taking out the biochar, recovering the biochar to be neutral, drying, mixing the dried biochar with an iron salt solution, fully reacting, drying and calcining to obtain the iron-modified biochar; the mass ratio of the dried biochar to iron in the iron salt solution is 0.28-0.84. The iron modified biochar has excellent phosphorus adsorption capacity in practical application, and has excellent phosphorus solid storage and continuous release capacity; the iron modified biochar can be used for soil phosphorus fixation and slow release, water pollution prevention and / or phosphate fertilizer saving, and can effectively promote plant growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biochar, and in particular to an iron-modified biochar for soil improvement, and a preparation method and application thereof. Background Art

[0002] Phosphorus is one of the macronutrients necessary for plant growth and development, and is also one of the main factors affecting water eutrophication. In gardening and greening management, in order to ensure the plant landscape effect, a large amount of phosphorus-containing compound fertilizers are often applied, but only 5% to 30% can be absorbed by plants, and the surplus phosphorus is lost to the water environment through surface runoff, seepage, etc. However, most urban landscape water bodies are overall closed or semi-closed slow-flowing water bodies with poor fluidity, small water collection, simple ecological structure, and fragile ecological functions. Excessive phosphorus can easily lead to the proliferation of water fungi, causing water pollution and difficult to recover.

[0003] Biochar is a highly aromatic, insoluble, carbon-rich product formed by thermal cracking of agricultural and forestry waste and other biomass under anaerobic conditions. It has a large specific surface area, high ion exchange capacity, and abundant chemical functional groups. It can change the circulation and effectiveness of phosphorus through physical and chemical adsorption and desorption. Studies have shown that the adsorption of phosphorus by ordinary biochar is largely affected by its own physical and chemical properties, with low adsorption capacity and large differences between different types of biochar.

[0004] Therefore, there is an urgent need for a modified biochar that can be used as a soil phosphorus fixation material or for preparing biochar-based fertilizers. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and to provide an iron-modified biochar for soil improvement and a preparation method and application thereof.

[0006] The first object of the present invention is to provide a method for preparing iron-modified biochar.

[0007] The second object of the present invention is to provide iron-modified biochar prepared by the above preparation method.

[0008] The third object of the present invention is to provide the use of the above-mentioned iron-modified biochar in soil phosphorus fixation and slow release, prevention of water pollution and / or saving of phosphorus fertilizer.

[0009] The fourth object of the present invention is to provide a method for slow-release soil phosphorus fixation using iron-modified biochar.

[0010] In order to achieve the above object, the present invention is implemented by the following scheme:

[0011] A method for preparing iron-modified biochar, comprising:

[0012] After the biochar is soaked in an acid solution, the biochar is taken out and restored to neutrality, and then dried. After the dried biochar is mixed with an iron salt solution and fully reacted, the biochar is dried and calcined to obtain iron-modified biochar;

[0013] The mass ratio of the dried biochar to the iron in the iron salt solution is 0.28 to 0.84.

[0014] Preferably, the iron salt solution is ferric chloride solution.

[0015] More preferably, the concentration of the ferric chloride solution is 0.8-1.2 mol / L.

[0016] Further preferably, the concentration of the ferric chloride solution is 1 mol / L.

[0017] Preferably, the biochar is walnut shell charcoal, rice straw charcoal and / or wood charcoal.

[0018] More preferably, when the biochar is walnut shell charcoal, the mass ratio of the dried biochar to the iron in the iron salt solution is 0.28; when the biochar is rice straw charcoal and / or wood charcoal, the mass ratio of the dried biochar to the iron in the iron salt solution is 0.56.

[0019] Preferably, the acid solution is a hydrochloric acid solution.

[0020] More preferably, the concentration of the hydrochloric acid solution is 0.5 to 1.5 mol / L.

[0021] Further preferably, the concentration of the hydrochloric acid solution is 1 mol / L.

[0022] Preferably, the mass volume ratio of the biochar to the acid solution is 1 g: 8-12 mL.

[0023] More preferably, the mass volume ratio of the biochar to the acid solution is 1 g:10 mL.

[0024] Preferably, the biochar is soaked in the acid solution for 1 to 2 hours.

[0025] More preferably, the biochar is soaked in the acid solution for 1 hour.

[0026] Preferably, the drying is performed at 75°C.

[0027] Preferably, the dried biochar is mixed with the iron salt solution, stirred thoroughly, and then allowed to stand for 18 hours.

[0028] The present invention also seeks to protect the iron-modified biochar prepared by any of the above-mentioned preparation methods.

[0029] The present invention also seeks to protect the use of the above-mentioned iron-modified biochar in soil phosphorus fixation and slow release, prevention of water pollution and / or saving of phosphate fertilizer.

[0030] The present invention also claims a method for slow-release soil phosphorus fixation using iron-modified biochar, comprising the following steps:

[0031] S1. After the iron-modified biochar according to claim 6 is mixed with potassium dihydrogen phosphate solution and fully reacted, the solid is collected by solid-liquid separation, and dried to obtain phosphorus-rich iron-modified biochar;

[0032] S2. applying the phosphorus-rich iron-modified biochar obtained in step S1 to the vicinity of the plant root system at an application amount of 1% to 2%;

[0033] The application amount is the percentage of the mass of the phosphorus-iron modified biochar to the soil mass.

[0034] Preferably, the concentration of the potassium dihydrogen phosphate solution in step S1 is 100-400 mg / L.

[0035] More preferably, the concentration of potassium dihydrogen phosphate is 263 mg / L.

[0036] Preferably, the mass volume ratio of the iron-modified biochar and the potassium dihydrogen phosphate solution in step S1 is 1-10 g: 10-50 mL.

[0037] More preferably, the mass volume ratio of the iron-modified biochar and potassium dihydrogen phosphate solution is 1 g:5 mL.

[0038] Preferably, the sufficient reaction in step S1 is specifically: constant temperature oscillation at 180 r / min at 25° C. for 24 hours.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention provides a method for preparing iron-modified biochar, comprising: soaking biochar in an acid solution, taking out the biochar and restoring it to neutrality, drying, mixing the dried biochar with an iron salt solution for sufficient reaction, drying and calcining to obtain iron-modified biochar; the mass ratio of the dried biochar to the iron in the iron salt solution is 0.28 to 0.84. The iron-modified biochar has excellent phosphorus adsorption capacity, excellent phosphorus storage and sustained release capacity in practical applications; the iron-modified biochar can be used for soil phosphorus fixation and slow release, prevention of water pollution and / or saving of phosphorus fertilizer, and can effectively promote plant growth. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The scanning electron microscope result image of WSB in Example 1;

[0042] Figure 2This is the scanning electron microscope result of WSB-0.28 in Example 1;

[0043] Figure 3 This is the scanning electron microscope result of WSB-0.56 in Example 1;

[0044] Figure 4 This is a scanning electron microscope result image of WSB-0.84 in Example 1;

[0045] Figure 5 The scanning electron microscope result image of RSB in Example 1;

[0046] Figure 6 This is the scanning electron microscope result of RSB-0.28 in Example 1;

[0047] Figure 7 This is the scanning electron microscope result of RSB-0.56 in Example 1;

[0048] Figure 8 This is a scanning electron microscope result of RSB-0.84 in Example 1;

[0049] Fig. 9 This is the scanning electron microscope result of WB in Example 1;

[0050] Fig.10 This is the scanning electron microscope result of WB-0.28 in Example 1;

[0051] Fig.11 This is the scanning electron microscope result of WB-0.56 in Example 1;

[0052] Fig.12 This is the scanning electron microscope result of WB-0.84 in Example 1;

[0053] Fig.13 The infrared spectrum detection result diagram in Example 1; (a) is the FTIR result diagram of WSB, WSB-0.28, WSB-0.56 and WSB-0.84, (b) is the FTIR result diagram of RSB, RSB-0.28, RSB-0.56 and RSB-0.84, (c) is the FTIR result diagram of WB, WB-0.28, WB-0.56 and WB-0.84;

[0054] Fig.14 The X-ray diffractometer results in Example 1; (a) is the XRD result diagram of WSB, WSB-0.28, WSB-0.56 and WSB-0.84, (b) is the XRD result diagram of RSB, RSB-0.28, RSB-0.56 and RSB-0.84, (c) is the XRD result diagram of WB, WB-0.28, WB-0.56 and WB-0.84;

[0055] Fig.15 The test results of the walnut shell charcoal and the iron-modified walnut shell charcoal in Example 2 on the adsorption and desorption of soil; a is the result diagram of phosphorus adsorption, b is the result diagram of phosphorus desorption, and c is the result diagram of desorption rate;

[0056] Fig.16 The test results of the rice straw charcoal and the iron-modified rice straw charcoal on soil adsorption and desorption in Example 2 are shown in Figure 1; a is the result diagram of phosphorus adsorption, b is the result diagram of phosphorus desorption, and c is the result diagram of desorption rate;

[0057] Fig.17 The graphs are the test results of soil adsorption and desorption of the wood charcoal and iron-modified wood charcoal in Example 2; a is the result graph of phosphorus adsorption, b is the result graph of phosphorus desorption, and c is the result graph of desorption rate;

[0058] Fig.18 This is a schematic diagram of the acupuncture point application in Example 3. DETAILED DESCRIPTION

[0059] The present invention is further described in detail below in conjunction with the accompanying drawings and specific examples of the specification. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0060] Walnut shell charcoal (WSB, pyrolyzed at 400°C for 2 h under oxygen-limited conditions) used in the embodiments of the present invention was purchased from Guangdong Guangsen Carbon Technology Co., Ltd., rice straw charcoal (RSB, pyrolyzed at 400°C for 2 h under oxygen-limited conditions) was purchased from Henan Lize Environmental Protection Technology Co., Ltd., and wood charcoal (WB, pyrolyzed at 400°C for 2 h under oxygen-limited conditions) was purchased from Dalian Qunfang Horticulture Co., Ltd.

[0061] The test soil (garden green land soil) used in the embodiments of the present invention was collected from the 0-30 cm surface soil of Haizhu Wetland Phase I (113°20'58" east longitude, 23°4'58" north latitude) in Guangzhou City, Guangdong Province, and was naturally air-dried and then crushed and passed through a 1.0 mm sieve for later use;

[0062] The pH value of the test soil was 5.5, the electrical conductivity (EC) was 0.02mS / cm, the organic matter content was 16.6g / kg, the total nitrogen content of the soil was 1.03g / kg, the total phosphorus content of the soil was 0.53g / kg, the total potassium content of the soil was 33.31g / kg, the alkaline nitrogen content was 71.0mg / kg, the available phosphorus content was 8.4mg / kg, and the available potassium content was 88.6mg / kg.

[0063] Example 1 Preparation of iron-modified biochar

[0064] 1. Experimental Methods

[0065] 1. Preparation of iron-modified biochar

[0066] 10 g of walnut shell charcoal (WSB) was soaked in 100 mL of HCl (1 mol / L) for 1 h, the solid was collected by filtration and rinsed with distilled water until neutral, and then placed in an oven to dry at 75°C to obtain dried walnut shell charcoal.

[0067] The dried walnut shell charcoal was added with 1 mol / L FeCl 3 The solution was stirred with a magnetic stirrer for 1 h, then allowed to stand for 18 h, the solid was collected by filtration and dried, then transferred into a porcelain crucible and calcined in a muffle furnace at 300 °C for 2 h to obtain iron-modified walnut shell charcoal (WSB-0.28); the dried walnut shell charcoal and FeCl 3 The mass ratio of iron in the solution is 0.28.

[0068] The dried walnut shell charcoal was mixed with FeCl 3 The mass ratio of iron in the solution was adjusted to 0.56, and WSB-0.56 was prepared according to the above method; the dried walnut shell charcoal was mixed with FeCl 3 The mass ratio of iron in the solution was adjusted to 0.84, and WSB-0.84 was prepared according to the above method.

[0069] Walnut shell charcoal (WSB) was replaced by rice straw charcoal (RSB) and wood charcoal (WB) in sequence, and their interactions with FeCl 3 The mass ratios of iron in the solution were 0.28, 0.56 and 0.84. RSB-0.28, RSB-0.56, RSB-0.84, WB-0.28, WB-0.56 and WB-0.84 were prepared according to the above method.

[0070] 2. Testing of Iron-modified Biochar

[0071] The surface morphologies of WSB, RSB, WB, WSB-0.28, WSB-0.56, WSB-0.84, RSB-0.28, RSB-0.56, RSB-0.84, WB-0.28, WB-0.56 and WB-0.84 prepared in step 1 were observed using a high-resolution field emission scanning electron microscope (SEM, Merlin, Zeiss, Germany), and the elemental composition of the biochar surface was determined using an energy spectrometer (X-MaxN20 dual detector system, Oxford Instruments, UK).

[0072] The specific surface areas of WSB, RSB, WB, WSB-0.28, WSB-0.56, WSB-0.84, RSB-0.28, RSB-0.56, RSB-0.84, WB-0.28, WB-0.56 and WB-0.84 prepared in step 1 were determined using a fully automatic specific surface area and pore size tester (BET, ASAP 2460 / 2020, Mack, UK), and the contents of C, H, N and S elements were determined using an elemental analyzer (Vario EL cube, Elementar, Germany).

[0073] The surface functional groups of WSB, RSB, WB, WSB-0.28, WSB-0.56, WSB-0.84, RSB-0.28, RSB-0.56, RSB-0.84, WB-0.28, WB-0.56 and WB-0.84 prepared in step 1 were determined using an infrared spectrometer (FTIR, VERTEX 33, Buker, Germany).

[0074] The crystal structures of WSB, RSB, WB, WSB-0.28, WSB-0.56, WSB-0.84, RSB-0.28, RSB-0.56, RSB-0.84, WB-0.28, WB-0.56 and WB-0.84 prepared in step 1 were determined by X-ray diffractometer (XRD, X'Pert PRO MRD, PANalytical, The Netherlands).

[0075] 2. Experimental Results

[0076] The scanning electron microscopy results are shown in Figure Figures 1 to 12 As shown, Figure 1 This is the scanning electron microscope result of WSB; Figure 2 This is the scanning electron microscope result of WSB-0.28; Figure 3 This is the scanning electron microscope result of WSB-0.56; Figure 4 This is the scanning electron microscope result of WSB-0.84; Figure 5 This is the scanning electron microscope result of RSB; Figure 6 This is the scanning electron microscope result of RSB-0.28; Figure 7 This is the scanning electron microscope result of RSB-0.56; Figure 8 This is the scanning electron microscope result of RSB-0.84; Fig. 9 This is the scanning electron microscope result of WB; Fig.10 This is the scanning electron microscope result of WB-0.28; Fig.11 This is the scanning electron microscope result of WB-0.56; Fig.12 This is the scanning electron microscope result of WB-0.84.

[0077] The results showed that the morphological characteristics of WSB, RSB and WB before modification were significantly different. Walnut shell charcoal had more tiny micropores, while rice straw charcoal and wood charcoal had evenly arranged pores and larger pores, among which wood charcoal had smaller pores. The surface morphology of all iron-modified biochars changed significantly compared with that before modification. Except for RSB-0.56 and RSB-0.84, a layer of particle structure was evenly formed on the surface of other modified biochars, indicating that iron was successfully loaded on the surface of these biochars. Compared with other iron-modified biochars, the surface particles of iron-modified WB were more uniform and dense, among which WB-0.84 was the most dense. In particular, large particles were formed on the surface of walnut shell charcoal.

[0078] The results of the energy spectrometer analysis are shown in Table 1.

[0079] Table 1 Spectrometer analysis results

[0080]

[0081] Note: In the same column of data, different lowercase letters represent significant differences among different treatments of the same biochar type (P<0.05).

[0082] The results showed that compared with unmodified WSB, RSB and WB, the mass percentage of C in the modified biochar decreased significantly, while the mass percentages of O and Fe increased, indicating that the modified biochar was loaded with iron oxides and oxyhydroxides.

[0083] The test results of the fully automatic specific surface area and pore size tester are shown in Table 2.

[0084] Table 2 Test results of fully automatic specific surface area and pore size test

[0085]

[0086] Note: In the same column of data, different lowercase letters represent significant differences among different treatments of the same biochar type (P<0.05).

[0087] The results showed that before modification, WSB had the largest specific surface area (26.7 m 2 / g), the smallest pore size (1.9nm); the specific surface area of ​​rice straw charcoal (13.4m 2 / g) is second, but the average pore size is the largest (13.3nm); wood charcoal has the smallest specific surface area (4.5m 2 / g), and Figure 1 The results of scanning electron microscopy are consistent with those shown.

[0088] After modification, the specific surface area of ​​walnut shell charcoal becomes smaller and the average pore size becomes larger, while the specific surface area of ​​rice straw charcoal and wood charcoal becomes larger after modification.

[0089] The analysis results of the element analyzer are shown in Table 3.

[0090] Table 3 Element analyzer analysis results

[0091]

[0092] Note: In the same column of data, different lowercase letters represent significant differences among different treatments of the same biochar type (P<0.05).

[0093] The results showed that the C content of the three biochars after modification was significantly reduced by 11% to 53%, and the C / N ratio was significantly reduced; the H content of walnut shell charcoal and wood charcoal was significantly reduced by 27% to 45% and 38% to 60%, which was basically consistent with the results of the energy spectrometer. In addition, the C / N of the biochars after modification was reduced, but the C / N of the iron-modified biochar was still greater than 25; at the same time, the H / C ratio of the iron-modified WSB was the smallest, indicating that the iron-modified WSB had the strongest aromaticity and a more stable structure.

[0094] Infrared spectrum detection results (FTIR) as shown Fig.13 As shown, (a) is the FTIR result graph of WSB, WSB-0.28, WSB-0.56 and WSB-0.84, (b) is the FTIR result graph of RSB, RSB-0.28, RSB-0.56 and RSB-0.84, and (c) is the FTIR result graph of WB, WB-0.28, WB-0.56 and WB-0.84.

[0095] The results showed that the hydroxyl groups (3000~3665cm -1 ), C=C, C=O on aromatic carbon (1627cm -1 ) and Si-O-Si(466cm -1 ) vibration peak intensities increased significantly; the number of hydroxyl groups and C=C double bonds on the surface of WSB-0.28 was significantly higher than that of WSB-0.56 and WSB-0.84. In addition, at 592 cm -1 A new peak appeared at the position, which corresponds to the stretching vibration of Fe-O, indicating that iron oxides were successfully loaded on the biochar surface. In the iron-modified WSB, the Fe-O vibration peak intensity of WSB-0.84 was slightly higher than that of WSB-0.28 and WSB-0.56; in the iron-modified RSB, the Fe-O vibration peak intensities of RSB-0.28, RSB-0.56 and RSB-0.84 were roughly equivalent, and significantly weaker than those of the other two biochars, indicating that there were fewer iron oxides attached to the RSB surface, which was consistent with the Figure 1 The scanning electron microscopy characterization results are consistent with those shown; in the iron-modified WB, due to the presence of a certain amount of iron elements attached to the pores of WB-0.28, the Fe-O vibration peak intensity of WB-0.28 is significantly higher than that of WB-0.56 and WB-0.84.

[0096] The X-ray diffractometer result diagram (XRD diagram) is as follows Fig.14 As shown, (a) is the XRD result diagram of WSB, WSB-0.28, WSB-0.56 and WSB-0.84, (b) is the XRD result diagram of RSB, RSB-0.28, RSB-0.56 and RSB-0.84, and (c) is the XRD result diagram of WB, WB-0.28, WB-0.56 and WB-0.84.

[0097] After the XRD results were retrieved in jade6.0, it was determined that the main active components of the prepared iron-modified biochar surface were Fe 2 O 3 (PDF#89-0597) in the iron-modified WSB, the Fe of WSB-0.56 and WSB-0.84 2 O 3 The diffraction peak intensity is comparable and slightly higher than that of WSB-0.28. In the iron-modified RSB, the Fe 2 O 3 The diffraction peak intensity of RSB-0.28 is much lower than that of RSB-0.56 and RSB-0.84, indicating that the Fe 2 O 3 less, which is consistent with the results of scanning electron microscopy and infrared spectroscopy; in the iron-modified WB, the Fe 2 O 3 The diffraction peak intensity is slightly higher than that of WB-0.56 and WB-0.84, which is consistent with the results of infrared spectrum but different from those of scanning electron microscopy, proving that there is Fe 2 O 3 Attached to the pores of WB-0.28.

[0098] Example 2 Effect of iron-modified biochar on soil phosphorus adsorption and desorption characteristics

[0099] 1. Adsorption and desorption experimental method

[0100] Phosphorus adsorption test: 1.25 g of the test soil was weighed and placed in a 50 mL centrifuge tube. WSB-0.28 prepared in Example 1 was added to the centrifuge tube at a final concentration of 2% (w / w). After mixing evenly, 25 mL of KH 2 PO 4 (phosphorus content is 60 mg / L), oscillate at 200 r / min for 24 h at 25 °C, then centrifuge at 4000 r / min for 3 min, filter, obtain residual soil sample and supernatant, determine the phosphorus concentration of the supernatant, and calculate the phosphorus adsorption amount Q according to formula I 1 ;

[0101] Formula I: Q 1 ={(c 0 -c)×V} / m;

[0102] Where m is the soil mass (g), c 0 Potassium dihydrogen phosphate solution (KH 2 PO 4 ) is the concentration of phosphorus in the supernatant (μg / mL), c is the concentration of phosphorus in the supernatant (μg / mL), and V is the volume of potassium dihydrogen phosphate solution (mL).

[0103] Phosphorus desorption test: Add 25 mL of saturated NaCl solution to the residual soil sample obtained from the adsorption test experiment, stir thoroughly until completely uniform, centrifuge at 4000 r / min for 3 min, filter and collect the solid. Add 25 mL of saturated NaCl solution to the solid, stir thoroughly until completely uniform, centrifuge at 4000 r / min for 3 min, filter and collect the solid.

[0104] Solid 1 was mixed with 25 mL of KCl solution (0.01 mol / L), oscillated at 200 r / min for 24 h at 25 °C, centrifuged at 4000 r / min for 3 min, and the supernatant 1 was collected. The phosphorus concentration in the supernatant 1 was determined, and the phosphorus desorption amount Q was calculated according to formula II: 2 ; and calculate the desorption rate according to formula III.

[0105] Formula II: Q 2 =(c 1 ×V 1 ) / m;

[0106] where c 1 is the phosphorus concentration in supernatant 1 (μg / mL), V 1 is the volume of supernatant 1 (mL), and m is the mass of the test soil (g).

[0107] Formula III: Desorption rate = (phosphorus desorption amount Q 2 / Phosphorus adsorption amount Q 1 )×100%; wherein the phosphorus desorption amount and phosphorus adsorption amount are the measurement results for the same iron-modified biochar.

[0108] The final concentrations of WSB-0.28 were adjusted to 4% and 6%, respectively, and the phosphorus adsorption, desorption and desorption rates were determined according to the above method; WSB-0.28 was replaced with WSB, WSB-0.56, WSB-0.84, RSB, RSB-0.28, RSB-0.56, RSB-0.84, WB, WB-0.28, WB-0.56 and WB-0.84, respectively, and the phosphorus adsorption, desorption and desorption rates of each iron-modified biochar were determined according to the above method.

[0109] 2. Experimental Results

[0110] The test results of walnut shell charcoal and iron-modified walnut shell charcoal on soil adsorption and desorption are shown in the figure below. Fig.15 As shown, a is the result diagram of phosphorus adsorption, b is the result diagram of phosphorus desorption, and c is the result diagram of desorption rate.

[0111] The results showed that for the phosphorus adsorption capacity, the phosphorus adsorption capacity of the soil after being treated with iron-modified WSB (i.e., WSB-0.28, WSB-0.56 and WSB-0.84) was 309-933 μg / g, which was 3.3-9.9 times that of the soil treated with unmodified WSB (99-121 μg / g), indicating that iron-modified WSB significantly improved the soil's adsorption capacity for phosphorus. Under the same soil addition amount, the phosphorus adsorption capacity of the soil treated with WSB-0.28 was significantly higher than that of the soil treated with WSB-0.56 and WSB-0.84 (P < 0.05); when the addition amount of iron-modified biochar (final concentration) increased from 2% to 4%, the phosphorus adsorption capacity of the soil treated with WSB-0.28 and WSB-0.56 increased by 108 μg / g and 122 μg / g, respectively, but when the addition amount increased to 6%, the phosphorus adsorption capacity no longer increased significantly (P > 0.05); while the phosphorus adsorption capacity of the soil treated with WSB-0.84 increased significantly with the increase of the addition amount (P < 0.05).

[0112] Regarding phosphorus desorption, the phosphorus desorption amount of the soil treated with iron-modified WSB was 40-71 μg / g, which was 1.5-2.9 times that of the soil treated with unmodified WSB. At the same addition amount, the phosphorus desorption amount of the soil treated with WSB-0.28 was significantly lower than that of the soil treated with WSB-0.56 and WSB-0.84 (P<0.05). The phosphorus desorption rate of the soil treated with iron-modified WSB was 5%-18%, which was 10%-44% of that of the WSB treatment. Among them, the phosphorus desorption rate of the soil treated with WSB-0.28 was the lowest (5%), which was lower than that of the WSB-0.56 (12%-18%) and WSB-0.84 (10%-15%) treatments. Only the WSB-0.84 treatment with an addition amount of 6% did not reach a significant level (P>0.05).

[0113] The test results of rice straw charcoal and iron-modified rice straw charcoal on soil adsorption and desorption are shown in the figure below. Fig.16 As shown, a is the result diagram of phosphorus adsorption, b is the result diagram of phosphorus desorption, and c is the result diagram of desorption rate.

[0114] The results showed that for the phosphorus adsorption amount, the phosphorus adsorption amount of the soil after being treated with RSB or iron-modified RSB (RSB-0.28, RSB-0.56 and RSB-0.84) increased significantly with the increase of the addition amount (P < 0.05); and the phosphorus adsorption amount of the soil after being treated with iron-modified RSB was 435-1168 μg / g, which was 3.1-6.1 times that of the soil treated with unmodified RSB (112-271 μg / g), indicating that iron-modified RSB significantly improved the soil's phosphorus adsorption capacity; under the same addition amount, the phosphorus adsorption amount of the soil after being treated with RSB-0.56 was significantly higher than that of the soil treated with RSB-0.28 and RSB-0.84 (P < 0.05), showing the best phosphorus adsorption capacity.

[0115] Regarding phosphorus desorption, when the final mass concentration of biochar added was 2% and 4%, there was no significant difference in the phosphorus desorption between the soil treated with iron-modified RSB and that treated with unmodified RSB; when the final mass concentration of biochar added was 6%, the phosphorus desorption of the soil treated with unmodified RSB was significantly higher than that of the soil treated with the three iron-modified RSBs; among them, there was no significant difference between RSB-0.28 and RSB-0.56 treatments, but both were higher than RSB-0.84.

[0116] The test results of soil adsorption and desorption of wood charcoal and iron-modified wood charcoal are shown in the figure below. Fig.17 As shown, a is the result diagram of phosphorus adsorption, b is the result diagram of phosphorus desorption, and c is the result diagram of desorption rate.

[0117] The results showed that for phosphorus adsorption, the phosphorus adsorption of soil treated with iron-modified WB (WB-0.28, WB-0.56 and WB-0.84) was 385-1000 μg / g, which was 6-11 times that of soil treated with unmodified WB (49-128 μg / g), indicating that iron-modified WB significantly improved the phosphorus adsorption capacity of soil (P < 0.05). Under the same soil addition amount, the phosphorus adsorption of soil treated with WB-0.56 was significantly higher than that of soil treated with WB-0.28 and WB-0.84 (P < 0.05), and the phosphorus adsorption of soil treated with all iron-modified WB increased significantly with the increase of addition amount (P < 0.05).

[0118] As for the phosphorus desorption amount, the phosphorus desorption amount of the soil treated with iron-modified WB was 69-93 μg / g, which was 1.6-2.0 times that of the soil treated with unmodified WB (39-50 μg / g); under the same addition amount, the phosphorus desorption amount of the soil treated with WB-0.84 was higher than that of the soil treated with WB-0.28 and WB-0.56, and only the 6% addition amount reached a significant level (P < 0.05); the desorption rate of the soil treated with iron-modified WB was 8%-19%, which was 8%-29% of the unmodified WB treatment (68%-93%), and the phosphorus desorption rate of the soil treated with WB-0.56 with a final addition mass concentration of 6% was the lowest.

[0119] comprehensive Figure 15 to Figure 17 The results show that the adsorption and desorption of phosphorus in the RSB-treated soil were higher than those in the WSB and WB-treated soils, and the difference in phosphorus adsorption reached a significant level (P < 0.05); for WSB-0.28, RSB-0.28 and WB-0.28, regardless of the final mass concentration of iron-modified biochar added, the phosphorus adsorption in the WSB-0.28-treated soil was significantly higher than that in the RSB-0.28 and WB-0.28-treated soils, except for the final mass concentration of 2%, the phosphorus desorption in the WSB-0.28-treated soil was lower than that in RSB-0.28 and WB-0.28; while the phosphorus adsorption in RSB-0.56 and RSB-0.84 were significantly higher than that in WSB-0.56, WSB-0.84, WB-0.56 and WB-0.84.

[0120] In summary, the performance of RSB-056 is better than that of RSB-0.28 and RSB-0.84; the performance of WB-0.56 is also better than that of WB-0.28 and WB-0.84, and the desorption amount and desorption rate of phosphorus in the soil treated with iron-modified WB are higher than those of other iron-modified biochars; and the adsorption capacity of phosphorus in the soil treated with WSB-0.28 is significantly better than that in the soil treated with WSB-0.56 and WSB-0.84.

[0121] Example 3 Effect of iron-modified walnut shell charcoal on plant growth

[0122] 1. Experimental Methods

[0123] 1. Preparation of phosphorus-rich iron-modified walnut shell charcoal (WSB-0.28+P)

[0124] 5 g of WSB-0.28 prepared in Example 1 was added to 25 mL of KH 2 PO 4 (263 mg / L), and oscillated at 200 r / min at 25°C for 24 h, and then centrifuged at 4000 r / min for 3 min. The solid was collected by filtration and dried at 80°C to obtain WSB-0.28+P.

[0125] 2. Potted plant test

[0126] Petunia seedlings (plug seedlings) were used as formula plants, with a column height of 3.5±0.5 cm and a crown width of 8.3±0.7 cm.

[0127] The petunia seedlings were transplanted into planting pots filled with 0.3 kg (dry weight) of vermiculite and expanded clay, with one plant planted in each pot. 25 mL of phosphorus-deficient Hoagland's nutrient solution was applied to each pot every week, and 25 mL of water was watered every other day; the mass ratio of vermiculite to expanded clay was 3:1.

[0128] Set up T1 group, T2 group and CK group respectively, and each group has 10 pots of plants, as follows:

[0129] Group T1: The WSB-0.28 prepared in Example 1 was applied around the root system of the petunia seedlings in the planting pot by hole application, 3 g each time, for a total of 2 applications, each time with an interval of 7 days, and the first application was on the 7th day after transplanting (recorded as the 1st day of the culture cycle); and 25 mL of phosphorus-deficient Hoagland's nutrient solution was applied every week, and 25 mL of water was watered every other day, and the culture cycle was 35 days; the hole application schematic diagram is shown as follows Fig.18 shown.

[0130] The only difference between group T2 and group T1 is that the WSB-0.28 prepared in Example 1 was replaced by an equal amount of WSB-0.28+P, and the rest of the treatments were exactly the same.

[0131] The only difference between the CK group and the T1 group is that the WSB-0.28 prepared in Example 1 was not added, and the other treatments were exactly the same.

[0132] Ten parallels were set up in each group. On the 35th day of cultivation, the plant height, crown width, relative chlorophyll content (SPAD), number of leaves and number of flowers of each group of petunias were tested. Then, destructive sampling was carried out on the petunias in each group, and they were divided into above-ground and underground parts. After being cleaned, they were dried to constant weight, and the above-ground dry weight (leaf dry weight) and underground dry weight (root dry weight) of each group of petunias were measured. The average value of the data of each group was taken as the growth index measurement result of the petunias in that group.

[0133] 2. Experimental Results

[0134] The results of the growth index determination of each group of petunia are shown in Table 4.

[0135] Table 4 Growth index determination results of petunia

[0136]

[0137] The results showed that compared with the control group (CK group), the plant height, leaf amount, flower amount and leaf dry weight of petunia treated with WSB-0.28 (T1 group) increased by 8%, 8%, 12% and 11%, respectively, indicating that the addition of WSB-0.28 had a certain promoting effect on the growth of petunia; compared with the T1 group, the plant height, crown width, leaf amount, flower amount, leaf dry weight and root dry weight of petunia treated with WSB-0.28+P (T2 group) increased by 9%, 36%, 64%, 91%, 156% and 146%, respectively, and the relative chlorophyll content of petunia leaves was significantly increased.

[0138] It shows that phosphorus-rich iron-modified walnut shell charcoal (WSB-0.28+P) can effectively promote plant growth.

[0139] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. For ordinary technicians in this field, other different forms of changes or modifications can be made based on the above descriptions and ideas. It is not necessary and impossible to list all the implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing iron-modified biochar, characterized in that: include: After the biochar is soaked in an acid solution, the biochar is taken out and restored to neutrality, and then dried. After the dried biochar is mixed with an iron salt solution and fully reacted, the biochar is dried and calcined to obtain iron-modified biochar; The mass ratio of the dried biochar to the iron in the iron salt solution is 0.28 to 0.

84.

2. The preparation method according to claim 1, characterized in that: The iron salt solution is ferric chloride solution.

3. The preparation method according to claim 2, characterized in that: The concentration of the ferric chloride solution is 0.8-1.2 mol / L.

4. The preparation method according to claim 1, characterized in that: The biochar is walnut shell charcoal, rice straw charcoal and / or wood charcoal.

5. The preparation method according to claim 1, characterized in that: The acid solution is a hydrochloric acid solution.

6. Iron-modified biochar prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the iron-modified biochar according to claim 6 in soil phosphorus fixation and slow release, prevention of water pollution and / or saving of phosphate fertilizer.

8. A method for slow-release soil phosphorus fixation using iron-modified biochar, characterized in that: The following steps are involved: S1. After the iron-modified biochar according to claim 6 is mixed with potassium dihydrogen phosphate solution and fully reacted, the solid is collected by solid-liquid separation, and dried to obtain phosphorus-rich iron-modified biochar; S2. applying the phosphorus-rich iron-modified biochar obtained in step S1 to the vicinity of the plant root system at an application amount of 1% to 2%; The application amount is the percentage of the mass of the phosphorus-iron modified biochar to the soil mass.

9. The method according to claim 8, characterized in that The concentration of the potassium dihydrogen phosphate solution in step S1 is 100-400 mg / L.

10. The method according to claim 8, characterized in that The mass volume ratio of the iron-modified biochar and the potassium dihydrogen phosphate solution in step S1 is 1-10 g: 10-50 mL.

Citation Information

Cited By

  • Biochar-iron composite material as well as preparation method and application thereof

    CN119955522A

  • Functionalized biochar material as well as preparation method and application thereof

    CN121949035A

  • Functionalized biochar material, preparation method and application thereof

    CN121949035B